Effects of American drama familiarity on Chinese people’s remote acculturation, attitudes, and watching intentions - Liang, Zeguang (International Journal of Innovative Research and Scientific Studies, 2024)
The study aims to examine the impacts of American drama familiarity on Chinese people’s remote acculturation to American culture, attitudes towards American dramas, and watching intentions of American dramas. A total of 358 survey data points from Chinese respondents were collected, and structural equation modeling (SEM) analysis was conducted in an effort to verify the research hypotheses. The research outcomes indicate that American drama familiarity significantly positively impacts American cultural orientation, attitudes towards American dramas, and watching intentions of American dramas, but does not significantly bear upon Chinese cultural orientation. American cultural orientation significantly positively affects attitudes towards American dramas. Additionally, Chinese cultural orientation significantly negatively influences attitudes towards American dramas. Attitudes towards American dramas engender significant positive effects on watching intentions for American dramas. American drama familiarity, the remote acculturation of Chinese people to American culture, attitudes towards American dramas, and watching intentions of American dramas are significantly interrelated. The research is only targeted at Chinese people, and the remote acculturation is bi-dimensional in this study. Thereby, the remote acculturation of local people to multiple cultures simultaneously ought to be delved into in subsequent research. It is recommended that stakeholders and marketers of American dramas take essential marketing measures to increase the familiarity of Chinese people with American dramas and promote their friendly attitudes toward American dramas. This study contributes to yielding empirical evidence for the interrelation between American dramas and the remote acculturation of Chinese people to American culture.